Fuel cell separators
Patent Information
- Application Number
- JP2021143893
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-03
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-09-03
AI Technical Summary
【0019】 本発明により、セパレータ全体において十分な耐食性を有し、発電体挟持部において低接触抵抗を有し、シール部材配設部において改善されたシール部材との接着性を有する、低コストの燃料電池用セパレータが提供される。
Smart Images

Figure 0007632192000002 
Figure 0007632192000003 
Figure 0007632192000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator for a fuel cell. [Background technology]
[0002] A fuel cell has a stack structure in which a certain number of unit cells that generate electromotive force by the reaction of fuel gas (hydrogen) and oxidant gas (oxygen) are stacked. Each unit cell has a membrane electrode assembly that has anode and cathode electrode layers (catalyst layers and gas diffusion layers) on both sides of an electrolyte membrane, and separators that are arranged on both sides of the membrane electrode assembly.
[0003] The fuel cell separator functions to electrically connect the unit cells in series and also functions as a partition wall that isolates the fuel gas, the oxidant gas, and the coolant from each other.
[0004] Various studies have been conducted on such fuel cell separators and fuel cells having such separators.
[0005] For example, Patent Document 1 discloses a separator for a fuel cell, the separator comprising a substrate made of Ti (titanium), a TiOx layer formed on the surface of the substrate, and a carbon-containing layer disposed on at least a portion of the surface of the TiOx layer, suppressing the occurrence of cracks in the TiOx layer, and having electrical conductivity.
[0006] Patent Document 2 discloses a fuel cell having a separator, the separator having a surface that has been subjected to NC treatment, the peripheral portion of the separator having a greater amount of carbon black than the inner portion of the separator, and at least a portion of the peripheral portion being bonded to a resin having a polar group.
[0007] Patent Document 3 discloses a separator made of a separator material including a stainless steel or iron substrate, a titanium layer on the surface of the substrate, and a mixed layer of conductive particles and titanium oxide on the surface of the titanium layer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2015-232937 A [Patent Document 2] JP 2019-192507 A [Patent Document 3] JP 2021-068539 A Summary of the Invention [Problem to be solved by the invention]
[0009] Generally, a fuel cell separator has a reactant gas flow path formed on one side thereof for flowing a reactant gas in a single cell, and a coolant flow path formed on the other side thereof for flowing a coolant in the single cell. Also, a reactant gas manifold opening functioning as an inlet and outlet for the reactant gas, and a coolant manifold opening functioning as an inlet and outlet for the coolant flow path are formed on the periphery of the fuel cell separator. Furthermore, around the reactant gas flow path, the coolant flow path, the reactant gas manifold opening, and the coolant manifold opening, sealing members are provided as appropriate to prevent leakage of each fluid.
[0010] Fuel cell separators need to be bonded to other components, such as resin sheets and gaskets, which are sealing members to prevent leakage of fluids such as the reactive gases H2 and O2 and the cooling medium, cooling water. Therefore, the adhesion and sealing reliability between the fuel cell separator and other components, such as adhesives used to bond the fuel cell separator to the sealing members, are important factors in determining the characteristics of the fuel cell separator.
[0011] In addition, the power generating element clamping portion of the fuel cell separator that clamps the power generating element is required to have low contact resistance, i.e., high electrical conductivity, in order to conduct the electricity generated by the power generating element, and further, to be corrosion resistant.
[0012] In order to impart these characteristics to fuel cell separators, a carbon layer / titanium layer is formed in an area including the power generator sandwiching portion that sandwiches the power generator in the fuel cell separator, with a mask covering areas other than the area, by carrying out physical vapor deposition (PVD). The corrosion resistance of the fuel cell separator is ensured by the titanium layer, and the low contact resistance of the fuel cell separator is ensured by the carbon layer.
[0013] However, while the prior art mentions the characteristics of each carbon / titanium layer, there is nothing that specifies the characteristics of each layer for each part of the separator in order to create a product with excellent productivity, and a fuel cell separator that possesses excellent characteristics and can be manufactured at low cost has not yet been revealed.
[0014] Therefore, an object of the present invention is to provide a low-cost separator for a fuel cell which has sufficient corrosion resistance throughout the separator, low contact resistance in the power generator clamping portion, and improved adhesion to the seal member in the seal member arrangement portion (i.e., adhesion between the seal member arrangement portion and the adhesive used to bond the seal member). [Means for solving the problem]
[0015] (Corrosion resistance) The power generator clamping portion of the fuel cell separator, which clamps the power generator, and the seal member arrangement portion, which is provided on the outer periphery of the power generator clamping portion and in which a seal member is arranged to seal the power generator clamping portion, require a titanium layer because excellent corrosion resistance is required. Therefore, by providing a titanium layer on each of the power generator clamping portion and the seal member arrangement portion, it is possible to impart just the right amount of corrosion resistance to the entire fuel cell separator.
[0016] (Low contact resistance, adhesion and seal reliability) In fuel cell separators, the power generator sandwiching portion that sandwiches the power generator requires low contact resistance, and therefore a carbon layer is necessary. On the other hand, in the seal member disposition portion that is provided on the outer periphery of the power generator sandwiching portion and that disposes a seal member that seals the power generator sandwiching portion, if a carbon layer is present in the same manner as in the power generator sandwiching portion, adhesion to the seal member and sealing reliability will decrease. Therefore, in fuel cell separators, by providing a carbon layer in the power generator sandwiching portion but not providing a carbon layer in the seal member disposition portion, it is possible to provide the right amount of low contact resistance, adhesion, and sealing reliability according to the requirements of each portion.
[0017] As a result of examining various means for solving the above-mentioned problems, the inventors have discovered that by manufacturing a fuel cell separator having a power generator clamping portion that clamps the power generator, and a seal member placement portion that is provided on the outer periphery of the power generator clamping portion and in which a seal member that seals the power generator clamping portion is placed, by forming a titanium layer in the areas that will become the power generator clamping portion and the seal member placement portion, and then forming a carbon layer in the area that will become the power generator clamping portion where the titanium layer is formed, it is possible to manufacture at low cost a fuel cell separator that has sufficient corrosion resistance throughout the separator, low contact resistance, i.e. high conductivity, in the power generator clamping portion, and improved adhesion to the seal member in the seal member placement portion, and have completed the present invention.
[0018] That is, the gist of the present invention is as follows. (1) A fuel cell separator having a power generating unit clamping portion that clamps a power generating unit, and a seal member disposition portion that is provided on the outer periphery of the power generating unit clamping portion and that disposes a seal member that seals the power generating unit clamping portion, the power generating body holding portion includes a metal substrate, a titanium layer formed on a surface of the metal substrate, and a carbon layer formed on the titanium layer; the seal member disposition portion includes a metal substrate and a titanium layer formed on a surface of the metal substrate; In the seal member-disposed portion, the titanium layer is exposed on the surface. Separator for fuel cells. Effect of the Invention
[0019] The present invention provides a low-cost separator for a fuel cell which has sufficient corrosion resistance throughout the separator, low contact resistance in the portion where the power generator is sandwiched, and improved adhesion to the seal member in the portion where the seal member is disposed. [Brief description of the drawings]
[0020] [Figure 1] 1A and 1B are schematic diagrams showing A) suitable examples and B) unsuitable examples of a measurement method for X-ray diffraction analysis of a separator surface having a flow path shape. [Diagram 2] FIG. 1 is a schematic diagram of the Miller index planes of the (100) plane, (002) plane, and (101) plane originating from titanium, and the shapes and cross-sectional shapes formed. [Diagram 3] 1 is a diagram showing a schematic diagram of an embodiment of a fuel cell separator according to the present invention; [Figure 4] 1 is a scheme showing a method for producing a fuel cell separator in an embodiment. [Diagram 5] FIG. 1 is a diagram showing an outline of a test method for hot water peel strength (maximum peel strength in hot water at 95° C.). [Figure 6] 1 is a graph showing the relationship between the surface titanium ratio and hot water peel strength in a seal member-disposed portion of a fuel cell separator. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Preferred embodiments of the present invention will now be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. Note that the fuel cell separator of the present invention is not limited to the following embodiments, and can be embodied in various forms with modifications and improvements that can be made by those skilled in the art, without departing from the gist of the present invention.
[0022] The present invention relates to a fuel cell separator having a power generator clamping portion that clamps a power generator, and a seal member arrangement portion that is provided on the outer periphery of the power generator clamping portion and that arranges a seal member that seals the power generator clamping portion, wherein the power generator clamping portion comprises a metal substrate, a titanium layer formed on the surface of the metal substrate, and a carbon layer formed on the titanium layer, and the seal member arrangement portion comprises a metal substrate and a titanium layer formed on the surface of the metal substrate, and the titanium layer is exposed on the surface of the seal member arrangement portion.
[0023] In the present invention, the metal substrate is a metal substrate known in the art, for example, but not limited to, a metal (including an alloy), such as stainless steel (SUS: an alloy of iron, chromium, and nickel), etc. The metal substrate is preferably stainless steel, for example, SUS304.
[0024] By selecting stainless steel as the metal substrate for fuel cell separators, raw material costs can be reduced.
[0025] The thickness of the metal substrate is not limited, but is usually 0.05 mm to 0.2 mm, and preferably 0.08 mm to 0.12 mm.
[0026] By setting the thickness of the metal substrate within the above range, raw material costs can be reduced.
[0027] The metal substrate usually has an uneven shape for delivering fluids such as H2 and O2 as reactive gases and cooling water as a cooling medium. The difference between the unevenness of the uneven shape of the metal substrate is usually 10 μm to 500 μm, excluding the thickness of the metal substrate. In the fuel cell separator of the present invention, the thickness of the titanium layer and the carbon layer formed on the metal substrate is thinner than the thickness of the metal substrate, so that the shape of the fuel cell separator depends on the uneven shape of the metal substrate.
[0028] The thickness of the titanium layer formed on the surface of the metal substrate in the power generator clamping portion and the sealing member placement portion is not limited, but is usually 50 nm to 1000 nm, preferably 50 nm to 500 nm, on average. The average thickness of the titanium layer can be measured, for example, by cross-sectional TEM observation.
[0029] Setting the upper limit of the thickness of the titanium layer as described above makes it possible to obtain the effect of reducing the amount of titanium used, and also to prevent the film stress caused by the formation of the titanium layer from becoming too large, thereby suppressing the occurrence of cracks in the titanium layer and deformation of a substrate on which a titanium layer is laminated, such as a stainless steel substrate on which a titanium layer is laminated.
[0030] By setting the lower limit of the thickness of the titanium layer as described above, sufficient corrosion resistance can be ensured.
[0031] In the titanium layer of the present invention, the ratio (orientation ratio) of the (100) plane to the sum of the peak intensities of the (100) plane, (002) plane, and (101) plane derived from titanium in an X-ray diffraction analysis of the separator surface, divided by their relative intensities, can usually be 16.9% or more, and preferably 20.0% or more.
[0032] Here, the method for X-ray diffraction analysis of the separator surface can be a conventional measurement method. Therefore, in the method for X-ray diffraction analysis of the separator surface, the separator surface to be measured is a portion suitable for X-ray diffraction analysis (a portion without curvature, for example, a flat portion, or a direction without curvature).
[0033] For example, when the separator to be measured has a flow path shape, the incident X-ray is incident on the separator so that the diffracted X-ray does not include information about the curvature of the separator flow path. As an example, FIG. 1 shows A) an appropriate example and B) an inappropriate example of a measurement method for X-ray diffraction analysis of the surface of a separator having a flow path shape. In FIG. 1, S indicates the separator flow path shape cross section. In FIG. 1A, the X-ray is incident on the convex part (top part) of the separator in the y-axis direction (direction perpendicular to the flow path direction), and the incident X-ray is diffracted in the y-axis direction at the separator. In the case of FIG. 1A, the incident X-ray is incident on the convex part of the separator in a direction perpendicular to the flow path direction, so the obtained diffracted X-ray does not include the influence of the curvature based on the separator flow path shape. On the other hand, in FIG. 1B, the X-ray is incident on the convex part (top part) of the separator in the x-axis direction (direction parallel to the flow path direction), and the incident X-ray is diffracted in the x-axis direction at the separator. In the case of B) of Fig. 1, the incident X-rays are incident on the convex part of the separator in a direction parallel to the flow path direction, so the obtained diffracted X-rays may include the influence of the curvature based on the separator's flow path shape. Therefore, in the measurement method of X-ray diffraction analysis of the separator surface in the present invention, when the separator has a flow path shape, the measurement method of A) of Fig. 1 is used.
[0034] The relative intensity of each lattice plane derived from titanium means the theoretical diffraction intensity (theoretical value of diffraction intensity), and is a general theoretical value that can be calculated from the crystal structure of titanium. In other words, the relative intensity of the (100) plane derived from titanium is the diffraction intensity theoretically obtained when the (100) plane is irradiated with X-rays, the relative intensity of the (002) plane derived from titanium is the diffraction intensity theoretically obtained when the (002) plane is irradiated with X-rays, and the relative intensity of the (101) plane derived from titanium is the diffraction intensity theoretically obtained when the (101) plane is irradiated with X-rays. Here, the X-rays irradiated to each lattice plane are the same X-rays. Therefore, the relative intensity of each lattice plane derived from titanium can also be expressed as the ratio of the theoretical diffraction intensity of each lattice plane obtained when the same X-rays are irradiated to each lattice plane (i.e., the theoretical diffraction intensity of the (100) plane: the theoretical diffraction intensity of the (002) plane: the theoretical diffraction intensity of the (101) plane). The relative intensity of each lattice plane originating from titanium is the theoretical diffraction intensity when the same X-ray is irradiated. Therefore, as long as the XRD measurements are performed using the same X-ray, it is an inherent value that is basically independent of the XRD instrument or type of X-ray used.
[0035] Therefore, for example, when the relative intensity of the (101) plane originating from titanium is taken as 100, the relative intensity of the (100) plane originating from titanium can be calculated to be 25, and the relative intensity of the (002) plane originating from titanium can be calculated to be 30 (i.e., the theoretical diffraction intensity of the (100) plane: the theoretical diffraction intensity of the (002) plane: the theoretical diffraction intensity of the (101) plane = 25: 30: 100).
[0036] From the above, the ratio (orientation ratio) of the (100) plane to the sum of the peak intensities of the titanium-derived (100), (002), and (101) planes divided by their relative intensities is expressed by the following formula. (100) plane ratio (orientation ratio) (%) = {(Peak intensity of (100) plane / relative intensity of (100) plane) / [(Peak intensity of (100) plane / relative intensity of (100) plane)+(Peak intensity of (002) plane / relative intensity of (002) plane)+(Peak intensity of (101) plane / relative intensity of (101) plane)]}×100
[0037] Furthermore, in a titanium layer containing titanium formed on the surface of a metal substrate, the ratio (orientation ratio) of the titanium-derived (002) plane to the total value obtained by dividing the peak intensities of the titanium-derived (100), (002), and (101) planes by their relative intensities in an X-ray diffraction analysis of the separator surface can usually be 61.0% or less, and preferably 40.0% or less.
[0038] The ratio (orientation ratio) of the titanium-derived (002) plane to the sum of the peak intensities of the titanium-derived (100), (002), and (101) planes divided by their relative intensities is expressed by the following formula, as described above. (002) plane ratio (orientation ratio) (%) = {(Peak intensity of (002) plane / relative intensity of (002) plane) / [(Peak intensity of (100) plane / relative intensity of (100) plane)+(Peak intensity of (002) plane / relative intensity of (002) plane)+(Peak intensity of (101) plane / relative intensity of (101) plane)]}×100
[0039] In the titanium layer formed on the surface of the metal substrate, the ratio (orientation ratio) of the (100) plane and / or the (002) plane to the sum of the peak intensities of the (100) plane, (002) plane, and (101) plane derived from titanium in an X-ray diffraction analysis of the separator surface, which is within the above range, results in a fuel cell separator with high corrosion resistance. The corrosion resistance can be confirmed by the amount of iron (Fe) eluted in a elution test of the fuel cell separator.
[0040] Schematic diagrams of the Miller index planes of the (100), (002), and (101) planes originating from titanium, as well as the shapes and cross-sectional shapes formed are shown in Figure 2. As shown in Figure 2, an increase in the proportion of the (100) plane originating from titanium means that the proportion of titanium having a flat structure in the titanium layer increases, and a decrease in the proportion of the (002) plane originating from titanium means that the proportion of titanium having a columnar structure in the titanium layer decreases.
[0041] The titanium-containing titanium layer formed on the surface of the metal substrate may contain other components, such as C, N, H, O, Ar, Ag, Mo, Rh, Pd, Pt, Pb, Ru, Al, Ni, and Co. The titanium-containing titanium layer is preferably a titanium layer made of titanium.
[0042] The titanium layer, which contains titanium and is deposited on the surface of the metal substrate, ensures corrosion resistance.
[0043] In the power generating body sandwiching portion of the fuel cell separator of the present invention, the thickness of the carbon layer formed on the titanium layer surface is not limited, but is usually 10 nm to 300 nm, preferably 10 nm to 150 nm, on average. The average thickness of the carbon layer can be measured, for example, by cross-sectional TEM observation.
[0044] By setting the thickness of the carbon layer formed on the surface of the titanium layer of the power generator sandwiching portion within the above range, low contact resistance of the power generator sandwiching portion, i.e., high electrical conductivity, can be ensured.
[0045] In the fuel cell separator of the present invention, the titanium layer is exposed on the surface in the portion where the seal member is provided.
[0046] The surface titanium ratio in the seal member placement portion is usually 0.5 atomic % or more, preferably 1.0 atomic % or more, and more preferably 1.5 atomic % or more.
[0047] The surface titanium ratio in the seal member-provided portion can be measured by X-ray photoelectron spectroscopy (XPS).
[0048] By exposing the titanium layer to the surface in the sealing member disposition area, it is possible to ensure adhesion and sealing reliability with other members in the sealing member disposition area, such as an adhesive used to bond the sealing member.
[0049] An example of the fuel cell separator of the present invention is shown in Fig. 3. As shown in Fig. 3, the fuel cell separator of the present invention has a power generator clamping section 1 that clamps a power generator, and a seal member disposition section 2 that is provided on the outer periphery of the power generator clamping section 1 and disposes a seal member that seals the power generator clamping section 1, where the power generator clamping section 1 has a metal base 3, a titanium layer 4 formed on the surface of the metal base 3, and a carbon layer 5 formed on the titanium layer 4, and the seal member disposition section 2 has the metal base 3 and the titanium layer 4 formed on the surface of the metal base 3, and the titanium layer 4 is exposed on the surface of the seal member disposition section 2.
[0050] The fuel cell separator in the present invention is a component of a fuel cell (single cell), and is disposed on both sides of a membrane electrode assembly (electrolyte membrane, anode and cathode electrode layers disposed on both sides of the electrolyte membrane).
[0051] The fuel cell separator of the present invention is bonded, for example, with an adhesive, to components of a fuel cell known in the art, such as a membrane electrode assembly and a seal member, to produce a fuel cell.
[0052] A fuel cell manufactured using the fuel cell separator of the present invention can be used in various electrochemical devices such as solid polymer fuel cells.
[0053] The fuel cell separator of the present invention can be produced by a method including the steps of: (i) preparing a metal substrate; (ii) depositing titanium on the surface of the metal substrate to form a titanium layer; and (iii) depositing carbon in an area of the metal substrate on which the titanium layer is formed, which will become the power generator sandwiching portion, to form a carbon layer.
[0054] (i) preparing a metal substrate First, a metal substrate that will be the material for the fuel cell separator is prepared.
[0055] As the metal substrate, a metal substrate known in the art can be used, for example, but not limited to, a substantially rectangular plate made of metal (including alloy) can be used. As the metal substrate which is the material of the separator, a substantially rectangular plate made of stainless steel (SUS: alloy of iron, chromium, and nickel), for example, SUS304, is preferable.
[0056] By selecting a metal substrate as the material for the fuel cell separator, a titanium layer and a carbon layer can be formed on the metal substrate by PVD, as described below, and by selecting stainless steel as the metal substrate, the cost of manufacturing the separator can be reduced.
[0057] As the metal substrate, it is preferable to use a metal substrate that has been pressed in advance into the final shape of the fuel cell separator.
[0058] By using a pre-pressed metal substrate as the metal substrate, a fuel cell separator can be obtained without further pressing after the titanium layer and carbon layer are formed.
[0059] (ii) forming a titanium layer on the surface of the metal substrate; The titanium layer can be produced by forming a film on the metal substrate using a sputtering method under conditions in which (a) the UBM coil current value or (b) the bias voltage value applied to the metal substrate is controlled within a certain range.
[0060] The sputtering method is a type of physical vapor deposition method, and an example of the sputtering method is unbalanced magnetron sputtering (UBMS).
[0061] The unbalanced magnetron sputtering (UBMS) method is a sputtering method that enhances plasma irradiation to the substrate by intentionally making the magnetic field of the sputtering cathode unbalanced, making it possible to form dense thin films.
[0062] In the sputtering method, (a) the UBM coil current value for controlling the plasma intensity is usually 6.5A to 10A, and preferably 7.0A to 9.0A.
[0063] By setting the UBM coil current value in the sputtering method within the above range, it is possible to allow the titanium particles, which are the film-forming particles, to reach the metal substrate in a high-energy state. Therefore, even if a metal substrate having an uneven shape is used as the metal substrate, it is possible to stably obtain a highly corrosion-resistant fuel cell separator having a densified titanium layer in all of the convex portions (top portions), concave portions (bottom portions), and diagonal portions between the convex portions and the concave portions of the metal substrate, and in particular, a highly corrosion-resistant fuel cell separator in which the ratio (orientation ratio) of the (100) plane and / or the (002) plane to the sum of the values obtained by dividing the peak intensities of the titanium-derived (100) plane, (002) plane, and (101) plane by their relative intensities in the X-ray diffraction analysis of the separator surface described above is within the above range.
[0064] Further / alternatively, in the sputtering method, (b) the bias voltage applied to the metal substrate is greater than -700V and equal to or less than -150V. In the unbalanced magnetron sputtering method, a glow discharge is generated between a target (i.e., titanium) as a cathode and a metal substrate as an anode to form an inert gas plasma, for example, Ar plasma, and positively ionized Ar ions in the Ar plasma repel the target atoms, accelerating the target atoms to form a film on the surface of the metal substrate, so that a negative voltage is applied to the metal substrate as a bias voltage. In addition, in this specification, when expressing the level of a negative bias voltage, a bias voltage closer to 0V is expressed as "high bias voltage".
[0065] When a metal substrate having a concave-convex shape is used as the metal substrate, the lower the bias voltage applied to the metal substrate in the sputtering method, the thinner the thickness of the titanium layer formed in the oblique portion between the convex portion and the concave portion tends to be. Therefore, by setting the bias voltage applied to the metal substrate in the sputtering method within the above range, the titanium particles, which are the film-forming particles, can reach the metal substrate in a high-energy state, so that even if a metal substrate having a concave-convex shape is used as the metal substrate, a highly corrosion-resistant fuel cell separator having a densified titanium layer in all of the convex portion (top portion), the concave portion (bottom portion), and the oblique portion between the convex portion and the concave portion of the metal substrate, particularly a highly corrosion-resistant fuel cell separator having a ratio (orientation ratio) of the (100) plane and / or the (002) plane to the total value obtained by dividing the peak intensity of the (100) plane, the (002) plane, and the (101) plane derived from titanium by their relative intensity in the X-ray diffraction analysis of the separator surface described above, can be stably obtained.
[0066] In the sputtering method, the distance between the titanium target, which is the titanium raw material, and the metal substrate, particularly the convex portion (top portion) of the metal substrate, is usually 10 cm±1 cm.
[0067] Regarding the sputtering method, conditions other than those described above, such as the initial vacuum in the device chamber, cleaning conditions for the metal substrate surface (for example, argon bombardment treatment conditions), plasma generation gas conditions, film formation time, film formation temperature, etc., can be conditions known in the art (for example, see International Publication No. 2015 / 068776). Note that the longer the film formation time, the thicker the film will be, so the desired film thickness can be obtained by adjusting the film formation time.
[0068] (iii) forming a carbon layer by forming a carbon film on the region of the metal base on which the titanium layer is formed that will become the power generator clamping portion; In the step (iii), a carbon layer is formed by depositing carbon on the metal base material on which the titanium layer is formed, in an area that will become a power generator holding portion.
[0069] Here, the power generator clamping portion is a roughly rectangular portion of the fuel cell separator for clamping the power generator located in the center, and the sealing member disposition portion is a portion of the fuel cell separator that is provided on the outer periphery of the power generator clamping portion and that disposes a sealing member that seals the power generator clamping portion.
[0070] Therefore, the region that becomes the generator clamping portion is a region of the approximately rectangular plate-shaped metal base material for clamping an approximately rectangular generator that is smaller than the metal base material located in the center, and the region other than the region that becomes the generator clamping portion is the region on the periphery of the region that becomes the generator clamping portion, i.e., the region that becomes the sealing member arrangement portion.
[0071] In the step (iii), the area of the metal substrate other than the area to be the power generator clamping portion, i.e., the area to be the seal member arrangement portion, is masked by, for example, arranging a masking member, so that a carbon layer can be formed by depositing carbon in the area to be the power generator clamping portion, and the titanium layer is exposed on the surface in the seal member arrangement portion. The masking member can be arranged with a space between it and the metal substrate (the area to be the seal member arrangement portion in the metal substrate), and in this case, the plate-shaped masking member is arranged with a space parallel to the plate-shaped metal substrate. The degree of exposure of the titanium layer to the surface in the seal member arrangement portion, i.e., the surface titanium ratio in the seal member arrangement portion, can be adjusted by the distance between the masking member and the metal substrate (the area to be the seal member arrangement portion in the metal substrate).
[0072] The carbon layer can be formed by a process known in the art, such as a filterless arc ion plating (AIP) method.
[0073] Here, the filterless arc ion plating method is a method in which an ionized substance (the target is evaporated and ionized, hereinafter referred to as ionized evaporated substance) generated by an arc discharge caused between an anode and a target constituting a cathode is accelerated by applying a bias voltage to a metal substrate, and the ionized evaporated substance is formed into a film on the metal substrate.
[0074] The bias voltage in the filterless arc ion plating method can be usually −450 V to −250 V, preferably −350 V to −250 V. In the filterless arc ion plating method, similarly to the principle of applying a negative voltage as a bias voltage in the unbalanced magnetron sputtering method, a negative voltage is applied to the metal substrate in order to accelerate the positively ionized evaporative material to form a film on the surface of the metal substrate on which the titanium layer has been formed.
[0075] By setting the bias voltage in the filterless arc ion plating method within the above range, a denser carbon layer with lower contact resistance can be formed, and lower contact resistance can be ensured in the power generator clamping portion. The crystallinity of the carbon layer can be measured by, for example, Raman spectroscopy, X-ray diffraction, etc.
[0076] For the filterless arc ion plating method, for example, the initial vacuum in the device chamber, cleaning conditions for the metal substrate surface (for example, argon bombardment treatment conditions), plasma generation gas conditions, film formation time, film formation temperature, etc. can be conditions known in the art (for example, see JP 2008-204876 A). Note that, since the film thickness increases as the film formation time increases, the desired film thickness can be obtained by adjusting the film formation time. EXAMPLES
[0077] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.
[0078] I. Manufacturing of separators for fuel cells According to the procedure shown in FIG. 4, fuel cell separators No. 1 to 3 were manufactured.
[0079] (i) preparing a metal substrate As the metal substrate, stainless steel (SUS304) having an uneven surface formed in advance by pressing into the shape of a fuel cell separator was prepared.
[0080] (ii) A step of forming a titanium layer by depositing titanium on the surface of a metal substrate (surface treatment 1: deposition) After removing the passivation on the surface of the SUS304 metal substrate by Ar etching, a titanium layer was formed on the SUS using a sputtering method under the conditions of a UBM coil current value of 6.5 A and a bias voltage to the metal substrate of -250 V.
[0081] (iii) A step of forming a carbon layer by forming a carbon film on the region of the metal base material on which the titanium layer is formed that will become the power generator clamping portion (surface treatment 2, film formation) The areas of the metal substrate other than the area that would become the power generator clamping portion were masked by arranging a masking material, and a carbon layer was formed on the titanium layer using the AIP method in the area that would become the power generator clamping portion, thereby producing a separator for a fuel cell. The fuel cell separators Nos. 1 to 3 were manufactured by varying the distance between the masking member and the metal base material (the region of the metal base material where the seal member was to be disposed) in the step (iii).
[0082] Measurement of surface titanium ratio in the seal member arrangement area of fuel cell separator manufactured in II.I The surface titanium ratios in the seal member-disposing portions of the fuel cell separators Nos. 1 to 3 produced in I were measured by X-ray photoelectron spectroscopy (XPS).
[0083] III.Measurement of hot water peel strength (adhesion) of fuel cell separators manufactured in I
[0084] The hot water peel strength of each separator at the seal member placement portion was measured according to the outline of the hot water peel strength test method shown in Figure 5. In Figure 5, a maleic acid-modified olefin-based adhesive sheet was first sandwiched between two L-shaped separators (seal member placement portions) and heat-pressed for 4 seconds at 180°C to prepare a T-shaped peel test piece. The resulting peel test piece was then placed in hot water at 95°C, and a weight was attached to one of the separators as shown in Figure 5. The hot water peel strength was determined by measuring the weight of the weight at which the adhesive sheet and the separator peeled off.
[0085] Table 1 shows the surface carbon ratio, surface titanium ratio, surface oxygen ratio, and hot water peel strength results for the seal member arrangement portion of the fuel cell separator, and FIG. 6 shows the relationship between the surface titanium ratio and hot water peel strength for the seal member arrangement portion measured in II.
[0086] [Table 1]
[0087] From Table 1 and FIG. 6, it is clear that the hot water peel strength increases as the surface titanium ratio increases.
[0088] The hot water peel strength test results in Table 1 and Figure 6 are for maleic acid-modified olefin-based adhesive sheets, but the results are also applicable to epoxy-based, acrylic-based, vinyl acetate-based, polyamide-based, polyester-based, and polyvinyl alcohol-based adhesive sheets other than maleic acid-modified olefin-based adhesive sheets. [Explanation of symbols]
[0089] S: Separator flow passage cross section 1: Power generator clamping part 2: Sealing material installation section 3: Metal base material 4: Titanium layer 5: Carbon layer
Claims
[Claim 1] A fuel cell separator having a power generating unit sandwiching portion that sandwiches a power generating unit, and a seal member disposition portion that is provided on an outer periphery of the power generating unit sandwiching portion and that disposes a seal member that seals the power generating unit sandwiching portion, the power generating body holding portion includes a metal substrate, a titanium layer formed on a surface of the metal substrate, and a carbon layer formed on the titanium layer; the seal member disposition portion includes a metal substrate and a titanium layer formed on a surface of the metal substrate; In the seal member-disposed portion, the titanium layer is exposed on the surface. Separator for fuel cells.
Citation Information
Patent Citations
Separator for fuel cell, and the fuel cell
JP2008016228A
Separator for fuel cell and fuel cell
JP2015232937A
Method of manufacturing separator for fuel battery
JP2017191640A
Plasma device
JP2018098210A
Fuel battery cell
JP2019192507A